Protective effects of pentoxifylline on T-cell viability under inflammatory conditions. (9th August 2022) - Park, Sung-Joon; Choi, Sung-Hyuk; Cho, Young-Duck; Kim, Jung-Youn; Cho, Han-Jin; Kim, Kyung-Hwan; Kim, Won-Young
Introduction: Pentoxifylline (PTX) reduces the levels of pro-inflammatory cytokines; however, its effects on immune system is not well understood. The aim of this study was to investigate the effect of PTX on T cells under inflammatory conditions in co-culture with THP-1-derived macrophages. Methods: Toll-like receptor 4 (TLR4 ) and macrophage migration inhibitory factor (MIF) levels were measured after addition of PTX to lipopolysaccharide (LPS)-stimulated differentiated THP-1 cells. T cell viability and MIF levels were measured after PTX was added to prostaglandin E2 (PGE2 )-stimulated Jurkat T-cell leukemia line. Co-culture was conducted to determine the effect of LPS-stimulated differentiated THP-1 cells that are affected by PTX on Jurkat cells. To prevent the direct effects of LPS and PTX on Jurkat cells, LPS and PTX were washed from THP-1 cells before co-culture. T cell viability and interleukin-2 (IL-2) levels were determined in Jurkat cells. Results: Increase in the MIF concentration and TLR4 expression level in differentiated THP-1 cells stimulated with LPS were reversed after PTX addition. However, PTX did not improve T cell viability in PGE2 –stimulated Jurkat cells. Co-culturing Jurkat cell and LPS-stimulated differentiated THP-1 cells resulted in a decreased viability of T cells. The addition of PTX restored T cell viability to normal control levels and IL-2 expression level in Jurkat cells. Conclusion: LPS-stimulated THP-1-derived macrophages reduced the T cell viability under inflammation. However, PTX restored T cells viability and IL-2 back to normal levels. Therefore, the immunomodulatory action of PTX may be mediated by macrophage-T cell interactions.